Implementation of the MDLC Method in the Pronounce Arabic (Makhorijul Huruf) Application Using Macromedia in PAUD Awwalussalaam - Yayu Anggraeni; Selamat Riyadi; Siti Nur (Universitas Pendidikan Indonesia (UPI), 2023)
Education is one of the foundations in life that starts early. Early childhood education is a program that requires parents to introduce their children to various things, especially introducing Al-Qur'an recitation. This is shown as a coaching effort for children from birth to the age of six. In the learning process it often happens that a teacher has difficulty conveying material to students, especially introducing the Al-Qur'an. This is due to the relatively short time in the learning process. Therefore, the purpose of this study is to create a learning application using macromedia flash to introduce recitation of the Qur'an which can help teachers and parents of students in the learning process of children outside of learning hours. The method used in developing this application uses the multimedia development life cycle method with the Luther model which has six stages, namely, (1) Concept, (2) Design, (3) Material Collection, (4) Manufacture, (5) Testing, (6) Distribution. Starting from this problem, the method used can be one of the interactive learning materials designed to be as attractive as possible to arouse children's enthusiasm in learning the Pronounce Arabic (Makhorijul Huruf) of the Qur'an so as to improve the quality of learning and minimize the estimated time used in the learning process. The result of this research is an application to recognize the Makhorijul Huruf of the Qur'an which can assist teachers in conveying learning with new and interesting methods.